KUALITAS KUAT TEKAN BATUGAMPING KRISTALIN DAN BATUGAMPING TERUMBU DI DAERAH BANJARJO DAN SEKITARNYA, DONOMULYO, MALANG, JAWA TIMUR: Bahasa indonesia - Dapri Aminu; Obrin Trianda, S.T., MT; Paramitha Tedja Trisnaning. S.T; Mirza Adiwarman, S.T., M.T; Anggi Deliana Siregar, ST., MT (Retii, 2024)
The utilization of class C mining materials, especially crystalline limestone and reef limestone in the construction world plays a very important role in supporting a development project. In the research area, precisely in Banjarjo Village, Malang Regency, these mining materials have not been utilized optimally. Therefore, the researcher conducted this special study aimed at comparing the quality of each existing rock using the compressive strength test analysis method. Based on the results of the compressive strength test analysis carried out at the Sabo Testing Center Laboratory in Yogyakarta, a comparison of the compressive strength values ​​of crystalline limestone with a value of 549.441 kg/cm² - 1454.830 kg/cm² from four samples taken in different places and reef limestone has a compressive strength value of 449.593 kg/cm² - 640.866 kg/cm² from three samples taken in different places. Keyword : Crystalline Limestone, Reef Limestone, Compressive Strength Test